Households on Savings Market in Poland - Challenges and Opportunities - Wójcik, Ewa (Polskie gospodarstwa domowe na rynku oszczędności - wyzwania i możliwości, 2010)
The article addresses the issue of individual savings which is of key importance for current economies. The critical role of households is visible on the market as their decisions determine supply of goods and services. Competition is tough and households have ample opportunities to choose from. Their modest funds are invested in different instruments, but the structure of savings reflecting their preferences shows that their decisions are not based on sound financial knowledge and maturity. Consumption is a priority of households and they often cover expenditure with credits. Challenges and opportunities of savings market are discussed with reference to households' behaviour and its determinants with focus on specific features of Polish households.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 125, s. 170-190
Keywords: savings; households; financial instruments; consumption